Impact of Fracture Type on Clinical and Radiological Outcomes of Lateral Humeral Condyle Fractures - Altunkılıç, Tarık (My University, 2018)
Objective: The purpose of this study is to determine the impact of the fracture type on the clinical and radiological outcomes of lateral humeral condyle fracture in children.Materials and Methods: Eighty-four patients, followed-up for at least two-years, without additional injuries, were included in this study for retrospective analysis. Seventy-two underwent surgical treatment and 12 non-operative treatment. The average follow-up period was 72.8 months. The Jacob classification system was used to classify fractures, and the Dhillon scoring system was used to evaluate outcomes.Results: Among the 66 male and 18 female patients, of the mean age of 5.5 years, there were 36 type I, 21 type II and 27 type III fractures. Lateral spurring occurred in 30 patients. The carrying angle was in average 6.5 degrees. Valgus deformity was observed in three patients and the varus deformity in six. There were excellent functional results in 69 patients and good functional results in 15 patients. When the functional grading in the different fracture types was compared, no statistically significant difference was found (P>0.05). When the clinical and radiological results were compared with the different treatment methods (non-operative, closed reduction percutaneous fixation and open reduction internal fixation), there was not a statistically significant difference observed (P>0.05).Conclusion: In this study, it was concluded that there was no significant relationship between the initial fracture type and clinical results, and It was concluded that the efficiency of reduction and stability are more important than the fracture type in surgical treatment.
Keywords: Anatomi ve Morfoloji; Cerrahi; Ortopedi